Flexural Behaviour of Composite Beam-Column Connections (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study includes an experimental investigations for the behavior of composite beam-column connections atstatic condition. The goals were to evaluate the effect of using cold-formed steel sections (CFS) which encasing in concrete asa replacement to steel bars of beam segment, while steel tube filled with concrete (CFST) used as column segment.. Resultsshow an improve in cracking load, ultimate strength, and stiffness for composite specimens compared with specimen that usingsteel bars reinforcement under static condition